Blood pressure and heart rate response to two resistance training technique of different intensity - Moro, T.; Thomas, E.; Bosco, G. (European Journal of Sport Studies, 2013)
Regular practise of physical activity would contrast obesity and several related disease1, but exercise should be enjoyable and useful to be part of person`s lifestyle. It has been recently demonstrated that High Intensity Resistance Training (HIRT) may increase resting energy expenditure after exercise and may reduce Respiratory Ratio hence improving fat oxidation. The shorter exercise time commitment may help to reduce one major barrier to exercise that is the lack of time. The aim of this study was to verify if HIRT was a safety way of training by the monitoring of Blood Pressure (BP) and Heart Rate (HR) during one session of this kind of exercise and compare it to common protocols propose by ACSM Guidelines (TT). Twenty healthy volunteers performed one session of both type of RT: HIRT technique consists of 6 repetitions, 20" rest, 2/3 repetitions, 20" rest, 2/3 repetitions with 2'30. rest between sets; TT consisted of 3 sets of 15 repetitions with 1`15" rest between sets. We measured Blood Pressure and Heart Rate during exercise and we calculated mean arterial pressure (MAP) and the Rate Pressure Product (RPP); basal lactate was measured after each session. Subjects shown similar HR response to both training (HIRT=128,20±15,64; TT= 116,29±14,78), also minimal and maximal value weren`t significant different (HIRT= 89,50±18,39 and 149,33±16,26; TT=84,33±15,23 and 150,00±16,12). Any difference also in SBP (HIRT=134,82±13,90; TT= 128,87±12,46) or DBP (HIRT=73,38±10,90; TT=73,94±9,66) interesting was the analysis of maximal and minimal BP and MAP value: during HIRT subjects reach level of DBP minor than during TT (p<0.05) and MAP was significant higher than baseline (p<0.05) only in TT. Subjects showed the same cardiovascular response to different intensity of resistance training. Furthermore, DBP, that is the most important BP parameter, reached lower level during HIRT than TT. The results of this study suggest that HIRT could be a safety way of training, and it could be propose to contrast obesity.